Effect of Tropolone And Some Plants Extracts on Elastase Production From P. Aeruginosa Isolates (Journal of the College of Basic Education, 2025)
P.aeruginosa is a significant opportunistic pathogen known for its production of elastase, an enzyme that contributes to tissue damage and virulence. The increasing prevalence of antibiotic resistance necessitates the exploration of alternative antimicrobial agents, including natural compounds.To evaluate the antibacterial activity of tropolone and various plant extracts (garlic, onion, moringa, and leek) against elastase-producing isolates of P. aeruginosa (P79). isolates were collected and evaluated for their production of the elastase enzyme. Antibacterial activity was assessed using the disc diffusion method, with varying concentrations of tropolone and plant extracts. Minimum Inhibitory Concentration (MIC) values were determined to quantify the effectiveness of each compound against the bacterial isolates.All tested compounds exhibited varying degrees of antibacterial activity. Tropolone was the most effective, completely inhibiting bacterial growth at all concentrations tested (15.6 µg/mL). Garlic extract showed significant inhibition at higher concentrations (500 µg/mL and 62.5 µg/mL), while onion extract also demonstrated activity at elevated concentrations (1000 µg/mL and 31.2 µg/mL). Moringa extract inhibited growth at the highest concentration (500 µg/mL), whereas leek extract exhibited limited antibacterial activity across all concentrations.These findings support the exploration of natural compounds as alternatives to conventional antibiotics in the treatment of infections caused by this pathogen.